2017
DOI: 10.3389/fmed.2017.00126
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytokines in the Fibrotic Responses in Crohn’s Disease

Abstract: Crohn’s disease is an idiopathic disorder of the gut thought to be caused by a combination of environmental and genetic factors in susceptible individuals. It is characterized by chronic transmural inflammation of the terminal ileum and colon, with typical transmural lesions. Complications, including fibrosis, mean that between 40 and 70% of patients require surgery in the first 10 years after diagnosis. Presently, there is no evidence that the current therapies which dampen inflammation modulate or reverse in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 105 publications
0
28
0
Order By: Relevance
“…A randomized clinical trial showed no effects of anti-TNFα treatment on deep endometriosis-associated pain 18 . Various anti-TNFα agents have been used in clinical practice for the management of inflammatory bowel disease (IBD) for the last 20 years 46,47 . However, therapeutic strategies to block TNFα to prevent fibrostenosis in Crohn's disease have only been successful in animal models 48 .…”
Section: Discussionmentioning
confidence: 99%
“…A randomized clinical trial showed no effects of anti-TNFα treatment on deep endometriosis-associated pain 18 . Various anti-TNFα agents have been used in clinical practice for the management of inflammatory bowel disease (IBD) for the last 20 years 46,47 . However, therapeutic strategies to block TNFα to prevent fibrostenosis in Crohn's disease have only been successful in animal models 48 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the character of the inflammatory response changes over the course of IBD. Type 1 and type 17 immune responses are known to be involved in the induction of CD colitis 47 , 48 , while type 2 cytokines have been associated with tissue remodeling and more chronic fibrotic pathology 30 , 31 . Kugathasan et al found that a strong type 1 immune profile exhibited by the gut mucosa of CD patients experiencing their first symptoms shifts to a more type 2 polarized milieu in patients with long-standing disease 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-13 has been reported to be an inflammatory stimulus in UC 26 , 27 , recent clinical studies found that anti-IL-13 therapy was not effective for UC patients 28 , 29 . While IL-13 is not known to be an initial driver of CD, it has been implicated in tissue remodeling and fibrosis in CD 30 , 31 . IL-13 and other type 2 cytokines are upregulated in response to tissue injury and are important for dampening inflammation and promoting wound resolution and repair 23 , 32 34 , requirements for recovery from both UC and CD.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing intestinal tissue samples from fibrotic CD with UC and uninvolved intestinal tissue, IL-13 transcripts were highest in fibrotic CD, but the difference was not statistically significant [199]. Whether IL-13 is involved in CD-related complications such as intestinal stricturing and fistulizing disease, requires further investigations [198,200].…”
Section: Does the Increased Il-13 Response Contribute To Disease Pathmentioning
confidence: 99%